A hybrid guidance law of LOS acceleration feedback for missile against maneuvering targets. Issue 3 (3rd July 2017) - Liu, Xiangbin; Qu, Xiaoli
Abstract: A quantised backstepping robust guidance law of three-dimension(3-D) space for compound control of reaction control jets and aerodynamic surfaces is proposed to attenuate the unknown target manoeuvre in this paper. The presented guidance law guarantees that the rates of line of sight converge to a residual circle centred at the origin whose radius is depended on the target manoeuvres, quantised length and guidance law gains. The simulations are given to illustrate the effectiveness of the proposed guidance law.